TUNGARESHWAR: REPOSITORY OF WILD EDIBLE AND MEDICINAL PLANTS: - - D MAHADKAR, SHIVPRASAD; B RAUT, RUDRAKSHI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of this study were as follows: (1) Ethnomedicinal survey and documentation of wild edible plants from Tungareshwar through discussion with rural people as well as continuously field visits. (2) Documentation of medicinal value of wild edible plants was done by discussion with local medicine man and Vaidus. Methods: The ethnobotanical survey was carried out in areas of Tungareshwar Devrai from June 2021 to June 2022. The data collected through discussions and interviews with experienced persons and traditional healers. The data on wild edible plants were collected using preparation of questionnaire in local language and group discussions. Voucher specimens were collected during walk with informants. The collected plants were identified using standard floras. Results: Altogether 30 plants species belonging to 25 families were recorded. A total of 30 species of Edible Plants are documented. Out of them, 12 species are consumed as leafy vegetables, 13 are fruits/seed, two are edible tubers, two are roots, and seven species of flowers are used as a vegetable. All 30 plants documented along with their medicinal uses and food values. Conclusion: The present work documented 30 wild edible and medicinal plants. Out of these, most of the plants have medicinal values. Further, investigation on their phytochemical and nutraceutical studies may provide better nutritional and medicinal sources for future.